1990
DOI: 10.1002/ijch.199000015
|View full text |Cite
|
Sign up to set email alerts
|

Metal‐Metal Coordination Chemistry: Free Clusters of Group 12 Elements with Sodium

Abstract: A systematic study of the mass spectra of particles formed in a supersonic nozzle expansion of Zn, Cd, and Hg vapors together with Na was performed. The particles discussed in this paper contain only one heavy atom and less than 12 Na ligands. Mass spectra from the neutral particles were generated by photoionization at five wavelengths (250, 260, 280, 300, and 320 nm) with a slit width corresponding to 16.5 and 3.3 nm, respectively. The abundances were corrected to relative differential ionization cross‐sectio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

1992
1992
1996
1996

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 24 publications
0
9
0
Order By: Relevance
“…To obtain the neutral cluster abundances, the photoionization mass spectra recorded with monochromator slits of 5 mm (16.5-nm fwhm (full width at half-maximum)) were corrected using relative differential ionization cross sections obtained from photoionization efficiency (PIE) curves. 10 These were measured with both 5-mm and 2-mm slits (6.6-nm fwhm). Five-millimeterslit PIE measurements provided rough data for this correction, and from the 2-mm-slit measurements, ionization thresholds were extracted.…”
Section: Neutral Cluster Abundancesmentioning
confidence: 99%
See 1 more Smart Citation
“…To obtain the neutral cluster abundances, the photoionization mass spectra recorded with monochromator slits of 5 mm (16.5-nm fwhm (full width at half-maximum)) were corrected using relative differential ionization cross sections obtained from photoionization efficiency (PIE) curves. 10 These were measured with both 5-mm and 2-mm slits (6.6-nm fwhm). Five-millimeterslit PIE measurements provided rough data for this correction, and from the 2-mm-slit measurements, ionization thresholds were extracted.…”
Section: Neutral Cluster Abundancesmentioning
confidence: 99%
“…In previous work, it was shown that small sodium heteroclusters with one atom of Cd/Zn/Hg are van der Waals molecules, whereas the same heteroclusters with more than six atoms are metal-bonded clusters. 10 Such a transition could not be found for Li/Na or Na/K heteroclusters, however. 11,12 Experiments on very small CsAu clusters suggest that the ionic character is already developed in this small size range.…”
Section: Introductionmentioning
confidence: 96%
“…CLis [S]), composition dependent electron localization (e. g. Na,Cl,, x > y ) [6], as well as the molecular systematics of metal alloys [7]. Most extensively studied (apart from hetero s'-doped clusters) have been clusters containing a single halogen [8], oxygen [3] or s2 electron metal atom [1,2,7]. For these systems, the observed stability island series and ionization potential discontinuities can be rationalized to first order in terms of spherical jellium-on-jellium or jelliumon-insulator calculations [3,9].…”
Section: Systematics Of Monodoped Alkali Clustersmentioning
confidence: 99%
“…For these systems, the observed stability island series and ionization potential discontinuities can be rationalized to first order in terms of spherical jellium-on-jellium or jelliumon-insulator calculations [3,9]. These suggest centered heteroatom geometries for the observed ,,closed shell" stability islands such as Na9X (X = halogen) [8], CsloO [3] and NasM [1,2] (M = s2 electron metal). Within this picture, heteroatoms are either electron withdrawing (e.g.…”
Section: Systematics Of Monodoped Alkali Clustersmentioning
confidence: 99%
See 1 more Smart Citation